Roles of Spermatogonial Stem Cells in Spermatogenesis and Fertility Restoration - Diao, Lei; Turek, Paul J.; John, Constance M.; Fang, Fang; Reijo Pera, Renee A. (Frontiers in Endocrinology, 2022)
Spermatogonial stem cells (SSCs) are a group of adult stem cells in the testis that serve as the foundation of continuous spermatogenesis and male fertility. SSCs are capable of self-renewal to maintain the stability of the stem cell pool and differentiation to produce mature spermatozoa. Dysfunction of SSCs leads to male infertility. Therefore, dissection of the regulatory network of SSCs is of great significance in understanding the fundamental molecular mechanisms of spermatogonial stem cell function in spermatogenesis and the pathogenesis of male infertility. Furthermore, a better understanding of SSC biology will allow us to culture and differentiate SSCs in vitro, which may provide novel stem cell-based therapy for assisted reproduction. This review summarizes the latest research progress on the regulation of SSCs, and the potential application of SSCs for fertility restoration through in vivo and in vitro spermatogenesis. We anticipate that the knowledge gained will advance the application of SSCs to improve male fertility. Furthermore, in vitro spermatogenesis from SSCs sets the stage for the production of SSCs from induced pluripotent stem cells (iPSCs) and subsequent spermatogenesis.